Islamic political history-1 - Ameer, U.A.; Sabir, Mohamed Muhsin (Islamic publishing house, 2016)
The book analyses the fabricated claims made on Pius Caliphs in the early Islamic era with descriptive analysis method....
Islamiya arasiyal varalaaru
Keywords: Political History